Neutral alpha‐1, 4‐glucosidase and fructose levels contribute to discriminating obstructive and nonobstructive azoospermia in Chinese men with azoospermia. (26th November 2015) - Lei, B.; Xing, R.; Zhou, X.; Lv, D.; Wan, B.; Shu, F.; Zhong, L.; Wu, H.; Mao, X.
Summary: Nowadays, whether neutral alpha‐1, 4‐glucosidase (NAG) and fructose levels are contributed to discriminating obstructive and nonobstructive azoospermia in Chinese azoospermic patients remains unclear. In this study, we retrospectively analysed the levels of NAG and fructose in 229 patients with obstructive azoospermia and 415 patients with nonobstructive azoospermia from three different medical central. Results indicated that NAG and fructose levels in patients with nonobstructive azoospermia were significantly higher compared with those with obstructive azoospermia ( P  < 0.05). According to the reference value of NAG and fructose defined by the World Health Organization (WHO, 2010), decreased level of NAG was observed in 77.3% of patients with obstructive azoospermia, which was significantly higher than those with nonobstructive azoospermia (55.2%, P  < 0.0001). Low level of fructose was observed in 48.0% of patients with obstructive azoospermia, which is also obviously higher than those with nonobstructive azoospermia (31.8%, P  < 0.0001). Moreover, the decrease of both NAG and fructose was only recorded in 3.7% of patients with SCO syndrome, 5.0% of patients with severe hypospermatogenesis and 18.2% of patients with maturation arrest. Therefore, our results indicated that NAG and fructose levels are contributed to discriminating obstructive and nonobstructive azoospermia in Chinese patients based on the histological types of testes.